A customised digitally engineered solution for fixed dental rehabilitation in severe bone deficiency: A new innovative line extension in implant dentistry. Issue 10 (October 2017) - Gellrich, Nils-Claudius; Zimmerer, Rüdiger M.; Spalthoff, Simon; Jehn, Philipp; Pott, Philipp-Cornelius; Rana, Majeed; Rahlf, Björn
Abstract: Objectives: Numerous procedures including soft and hard tissue reconstructions are necessary to allow for final implant-borne dental rehabilitation in patients with severe alveolar atrophy or resected jaws. In these cases, customised digitally engineered patient solutions for fixed or removable dental rehabilitation provide an innovative line extension to conventional implant dentistry. Material and methods: A wax-up was performed on plaster models that were scanned by 3D laser. The generated stereolithographic files were then fused with the preoperative 3D imaging data. The individualised "dental" patient solutions were designed digitally and comprised a skeletonised anchorage system and a suprastructure connection system. Insertion of the implants was performed on an outpatient basis. Conventional implant-supported prosthodontic rehabilitation was performed. Results: This digital planning algorithm can be applied to manufacture individualised patient solutions. Similar to conventional implant-supported dentures, these implants can be equipped with individual suprastructure connection systems for internal conical connection, ball-retained attachment, and external conical (telescopic) connection. Conclusions: In patients with severe atrophy or resected jaws, particularly following ablative tumour surgery, customised digitally engineered solutions allow for an innovative, less invasive line extension to conventional implant dentistry. When conventional implant dentistry reaches its limits, they still offer a strategy for implant-borne dental rehabilitation.